Análise espacial da degradação ambiental no municipio de Capão do Leão, RS - Cruz, Ricardo Decker da (2011)
The nowadays model of development has as a basic principle an economically based growth focused in the technological development, having the GIP as the main indicator of development of a nation. This model is known for promoting an accelerated degradation of the quality of the environment under pressure. The present work aims the identification; quantification and classification of the severely degraded land in the Capão do Leão municipality RS, Brazil, through the use of geotechnologies. In order to achieve that, the following base layers were used: roads, hydrography, river basins, numerical terrain model, vegetation, geology, soils, and degraded land. The degraded land areas were identified and delineated in Google Earth images and subsequently characterized in the field. Through the degraded land data collected a land degradation classification scheme was conceived based on the causing agent, degradation degree, the activity status of the degrading agent, and the possibility and type of reclamation needed. Crossing the land degradation database with the other base maps generated new maps and information. A number of 746 degraded areas were identified, varying in size, shape and degree, totaling 474,9ha of severely degraded land, mostly due to mine activities (361,4 ha or 76% of the total) - sand, granite and gravel. Other important type of degradation were those of borrow materials (61,8 ha 13% of the total). Soil units more affected were those of Entisols and Ultisols, due to granite and gravel mining, respectively, and of Spodosols, located in the São Gonçalo plain, due to sand mining. From the total degraded areas, 224,7ha in 69 occurrences are in an extremely degree of degradation under strong or very strong erosive activity, needing a restoration that includes a continuous intervention with reconditioning of the surroundings, that in some cases may need a change of use.